2020
DOI: 10.2147/ccid.s284359
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nationwide Survey and Identification of Potential Stress Factor in Sensitive Skin of Chinese Women</p>

Abstract: Sensitive skin is characterized by uncomfortable sensations in response to a number of factors. We performed a large-scale study to investigate the prevalence of sensitive skin at all ages and the impacts of related factors across China. Methods: A nationwide sampling of the Chinese population aged over 18 was conducted. Subjects were categorized into sensitive and non-sensitive groups, and critical differences between these two groups were investigated. Results: In total, 22,085 questionnaires were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For example, a large survey of 22 556 women and 557 men, aged 18–80 years, revealed that the frequency of skin sensitivity increased with age, from 35.9% in those aged 18–20 years to 70.7% in those aged 71–80 years. The authors also reported that mild or heavy stress was associated with skin sensitivity 25 . Future surveys in older individuals are therefore of interest to examine the association between stress and skin preaging observed in the present survey of young women.…”
Section: Discussionmentioning
confidence: 54%
“…For example, a large survey of 22 556 women and 557 men, aged 18–80 years, revealed that the frequency of skin sensitivity increased with age, from 35.9% in those aged 18–20 years to 70.7% in those aged 71–80 years. The authors also reported that mild or heavy stress was associated with skin sensitivity 25 . Future surveys in older individuals are therefore of interest to examine the association between stress and skin preaging observed in the present survey of young women.…”
Section: Discussionmentioning
confidence: 54%
“…In a study reported in 2018 conducted in France among 5000 subjects, Misery and colleagues found that 59% of the responders declared they had very or fairly sensitive skin (66% of women and 51.9% of men), and SSS was more common in younger people [51]. In a study in China involving 23,113 individuals, Xiao and colleagues showed a steady decline in the prevalence of SSS in different age groups from 65.8% in the 21-30 age group to 29.3% in the 71-80 age group [67]. A study conducted in Korea showed a similar pattern, with a decrease in the prevalence of sensitive skin from 64.8% in individuals aged 15-29, to 48.7% in individuals ≥ 60 [46].…”
Section: Agementioning
confidence: 99%
“…1 The prevalence of SS is 49.6% in Chinese women. 2 Over 70% of subjects with SS have erythema, while individuals with pruritus and tingling account for 61% and 39%, respectively. 3 SS negatively impacts quality of patients' lives and imposes a heavy economic burden to both patients and society.…”
Section: Introductionmentioning
confidence: 99%
“…The skin can appear normal or be accompanied by erythema 1 . The prevalence of SS is 49.6% in Chinese women 2 . Over 70% of subjects with SS have erythema, while individuals with pruritus and tingling account for 61% and 39%, respectively 3 .…”
Section: Introductionmentioning
confidence: 99%